ANALISIS PENGARUH SIKAP KERJA, KARAKTERISTIK INDIVIDU DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KARYAWAN DI UNIVERSITAS MUHAMMADIYAH BENGKULU - Sri Ekowati; Subandrio Subandrio; Jippy Monica (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2021)
ABSTRACTThis research aims to find out the Analysis of Work Attitudes, Individual Characteistics and Organizational Culture Effect on Employee Productivity at Muhammadiyah University Bengkulu with quantitative approach.The object of this research is a permanent employee at Muhammadiyah University of Bengkulu with a method of sample withdrawal namely non probility sampling. The number of respondents in this study was 38 people. Method of collecting the data used through the questionnaire, and multiple linear regression data analysis techniques.The results of this study can be concluded that the variables of work attitudes, individual characteristics and organizational culture have a significant effect on the employeesproductivity of Muhammadiyah University of Bengkulu.keywords: workattitudes, individual characteristics, organizational culture and employee productivity.